DEVELOPING TEACHING MEDIA THROUGH POWTOON AS “TPACK” (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) FOR SPEAKING SKILL AT GRADE 8 STUDENTS OF SMPN 2 BANGUN PURBA - SUCI JUMIATI; NORA RONITA DEWI (State University of Medan, 2023)
The objective of this study is to develop PowToon as media for teaching at Grade 8 students of SMP N 2 Bangun Purba in speaking transactional text. This research was conducted based on educational research and development (R&D) through six steps, namely: gathering data, analyzing data, designing media, validating by the expert, revising media, and final product. The Instrument of Collecting Data was questionnaire. The finding showed that one video of PowToon was used to teach English writing to Junior High School. The developed media PowToon had been validated by two experts and the average score has gotten was 85%. It was categorized “Excellent” since that the developed to teaching media PowToon for speaking skills were suitable for the 8 grade students of SMPN 2 Bangun Purba.